Serological Status for Chlamydophila psittaci, Newcastle Disease Virus, Avian Polyoma Virus, and Pacheco Disease Virus in Scarlet Macaws (Ara macao) Kept in Captivity in Costa Rica - Herrera, I. (2002)
From 1998 to 1999, a total of 128 blood samples were collected from scarlet macaws (Ara macao), kept in captivity in 11 different aviaries located in six provinces of Costa Rica. The sera were examined for antibodies directed against Chlamydophila psittaci, Newcastle disease virus (NDV), avian polyoma virus (APV), and Pacheco disease virus (PDV). Testing by enzyme-linked immunosorbent assay (ELISA), showed 16 (12.39%) of the samples (n = 129) exhibited antibodies directed against C. psittaci. Employing haemagglutination inhibition tests for NDV antibodies, all of the samples were found to be negative. The prevalence of antibodies specific for APV was tested with a blocking ELISA and serum neutralization tests (SNT) and 12 of 128 samples (9.37%) were found to be positive with both tests. In SNT, two out of 128 samples (1.56%) were positive for PDV. This is the first description of the serological status in scarlet macaws in captivity in Costa Rica. The study demonstrates the absence of NDV antibodies in the birds investigated on one hand, but also indicates a health hazard for numerous avian species due to the risk of infections with C. psittaci, APV or PDV.